Smart Bed Design in Assisting Routine Control of Patient Health - Otoluwa, Afnan; Ayusta Lukita Wardani; Widiyartono, Mahendra; Rahmadian, Reza (Proceeding of International Joint Conference on UNESA, 2024)
Recently, healthcare institutions have started using robots and various sensors to improve service quality and work efficiency. There is no mattress or bed that can automatically control its patients regularly by monitoring pulse, temperature in one system. Can help care for patients who are experiencing hospitalization with the Smart Bed control. This Smart Bed will help health workers to monitor the condition, especially the patient's vital signs, and the results will be obtained in real time so that patients can be treated optimally. The MLX90614 sensor test results show an average error of 1.35% for the first person's body temperature (35.02 °C), 2.42% for the second person (34.56 °C), and 2.16% for the third person (35.24 °C). The MAX30100 sensor had an average error of 3.45% for the first person's pulse rate (81.2 bpm), 3.65% for the second person (82.4 bpm), and 4.08% for the third person (86.4 bpm). The MLX901614 temperature sensor had an average error of 0.37% when compared to the thermogun, showing an accuracy of about 99.63%. While the MAX30100 pulse sensor, compared to a pulse oximeter, has an average error of 1.82%, with an accuracy rate of about 98.18%. So it can be concluded that the smart bed is in the working order.